1996
DOI: 10.3382/ps.0751383
|View full text |Cite
|
Sign up to set email alerts
|

Virginiamycin and Caloric Density Effects on Live Performance, Blood Serum Metabolite Concentration, and Carcass Composition of Broilers Reared in Thermoneutral and Cycling Ambient Temperatures

Abstract: One experiment utilizing Cobb x Cobb male broilers was conducted to evaluate virginiamycin (VM; 0, 15, 20 ppm) and diet caloric density (CD; 2,945, 3,200 AMEn/kg) effects on broiler live performance, blood serum metabolites, and carcass composition. The starter period exposed birds to recommended brooding conditions, whereas from 3 to 7 wk birds were exposed to thermoneutral (TN, 24 C) or cycling temperature (CT, 24 to 35 C) environments (E). During the 21-d starter period, VM levels and high CD increased (P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 56 publications
3
3
0
Order By: Relevance
“…Suchy et al (2001) and Kurtoglu et al (2001) reported mean Ca levels similar to the mean values found in our experiment. Our values also fall within the physiological range as described by Belay and Teeter (1996). Lower values as compared with our results were reported by Koelkebeck and Odom (1995), Sahin et al (2002b), and Eren et al (2004).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Suchy et al (2001) and Kurtoglu et al (2001) reported mean Ca levels similar to the mean values found in our experiment. Our values also fall within the physiological range as described by Belay and Teeter (1996). Lower values as compared with our results were reported by Koelkebeck and Odom (1995), Sahin et al (2002b), and Eren et al (2004).…”
Section: Discussionsupporting
confidence: 84%
“…The values we obtained from all the housing systems ranged within mean values reported e.g. by Jerabek et al (1993), Koelkebeck and Odom (1995), Belay and Teeter (1996), Kaya et al (2001), Suchy et al (2001), Sahin et al (2002a), and Thiemel and Jelinek (2004). Substantially higher values were published by Eren et al (2004), whereas lower values were reported by Kurtoglu et al (2001).…”
Section: Discussionsupporting
confidence: 83%
“…In broiler chickens under condition of heat stress, enhanced growth performance with VM supplementation was likewise associated with decreased heat production and related heat distress mortality, and improved energetic efficiency. Belay and Teeter [ 25 ] suggested that observed response to VM supplementation was partly attributable to improved temperature homeostasis of chickens under conditions of heat stress. Consistent with this earlier work involving poultry, we likewise found that VM supplementation does in fact lower core temperatures in cattle.…”
Section: Resultsmentioning
confidence: 99%
“…Added in low doses to the feed of farm animals, they have been shown to increase daily weight gain and conversion of feed into body mass, leading to economic advantages for farmers 2,3,4,5 . However, there is an increasing trend to reduce this use of antibiotics in feedstuffs.…”
Section: Removing Antimicrobial Growth Promoters and The Rise Of Necrmentioning
confidence: 99%